Analisis Semantik Preposisi yang Digunakan dalam Buku "21 Lesson for the 21st Century" Karya Yuval Noah Harari - Febriana Aminatul Khusna; Sekar Lathifatul Aliyah (Musamus Journal of Language and Literature, 2021)
The use of corpus analysis is often used in various fields of linguistic studies. Semantic studies are one of the topics of corpus analysis. However this research is still rarely found in several references in journals. The reference in question is the use of semantic analysis on texts, books, conversations or speaking, novel and much more. Preposition is one element of language to compose sentences in language. The aim of this research is to investigate the study of meaning regarding prepositions in novels. The novel entitled â€œ21 Lesson for the 21st Centuryâ€ by Yuval Noah Harari is used in this research. In this novel, the researcher found tht there are 73 preposition and 10 common preposition that used in this novel. The words â€œof, in, that, for, on, as, with, by, about, fromâ€ are the common preposition that used in this novel. In this study, researchers will read the novel, then analyze it. This analysis used to look for prepositions and foods contained in prepositions. Alphabetis is also used to facilitate researchers in delivering research results.